PENGARUH EKSTRAKURIKULER KEPUTRIAN TERHADAP PENINGKATAN PRESTASI BELAJAR FIKIH, AKHLAK DAN SOFT SKILL REMAJA PUTRI DI SMA MA'ARIF KEC. SUKOREJO - Wardah In Amil Maulana; Muhammad Nur Hadi; Anang Solehuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the influence of girls' extracurricular activities on improving the learning achievement of jurisprudence, morals and soft skills for young women at Ma'arif High School, Sukorejo District. The research uses a quantitative approach with an ex post facto type. Data collection techniques are carried out through observation, questionnaires, interviews and documentation. Data analysis uses validity, reliability, classical assumption tests, F tests, t tests, and linear regression with the help of the SPSS application. The results of the research show that extracurricular activities in women's affairs have a positive influence on improving students' learning achievement in jurisprudence, forming morals and developing soft skills. The results of the F test show a significance value of 0.000 <0.05, which means the research variables have a simultaneous effect. The fiqh learning achievement variable has the most dominant influence with a significance value of 0.011 <0.05. Thus, girlish extracurriculars can be an effective means of forming religious character, improving academic quality, and developing the social skills of young women.